MEWUJUDKAN KECAMATAN LENGKITI SEBAGAI PUSAT PENGHASIL OLAHAN JAGUNG DI KABUPATEN OKU (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Corn is one of Indonesia's mainstay food crops, apart from rice and soybeans. Corn is a plant that has great potential in Indonesia. Corn has a relatively high source of carbohydrates and calories (energy). Corn carbohydrate content ranks fourth after rice, sweet potatoes and cassava. Corn (Zea mays) is one of the most important carbohydrate-producing food crops in the world, apart from wheat and rice. For residents of Central and South America, corn kernels are a staple food, as are some people in Africa and some people in Indonesia. At present, corn has also become an important component of animal feed. Another use is as a source of food oil and a base for cornstarch. The need for corn as a raw material for making corn flour or corn flour always increases every year, because the content of nutrients and vegetable protein in corn makes this snack very popular with many people. The nutritional content in corn is as high as the nutritional content in whole corn, the difference is that the fiber in the corn dregs is higher. Even so, the vegetable protein in corn dregs is still there and if it is processed into confectionery it is still beneficial for the growth of the human body. The high vitamin B in corn is very good for the development and development of children. Corn is a commodity that is usually processed into a variety of foods, one of which is corn chips. Although corn chips have long been known, their marketing distribution is still on a local scale as a result of which corn chips are not well known by the public. It is still rare for people to use corn to be processed into chips. Generally, corn is processed into pop corn, flour, and others for animal feed needs. Since entering the covid pandemic, many businesses have been affected, thereby reducing sales turnover, including corn farming. The solution given to farmers is through processed corn into other forms of food that can be sold for profit, one of which is corn flakes. The solution provided to partners is through training in making corn chips, business management, digital-based marketing for corn chips in order to attract market attention. This activity gave rise to a new business that could become a mainstay product typical of the Lengkiti District, so that in the future it is hoped that it will be able to realize the Lengkiti District as a corn processing center. With attractive packaging and online marketing, it is hoped that it will be able to increase the income of corn farmers in Lengkiti District, especially after the covid pandemic.